SSA 05-4 DIFFERENCES IN MANAGEMENT OF HYPERTENSION BETWEEN ETHNIC GROUPS. (September 2016) - Rayner, Brian
Abstract : Although the consequences of hypertension are universal, Blacks (African Americans or Indigenous Africans) have been the subject of a differential approach to causation, outcome and treatment. Blacks have a greater propensity to salt sensitivity and suppressed plasma renin suggesting a predisposition to Na retention by the kidney. As a result blood pressure (BP) response to diuretics and amlodipine is better than inhibitors of the renin-angiotensin-system in monotherapy. Target organ damage is more frequent and blood pressure (BP) is more difficult to control despite more intensive therapy. The kidney filters approximately 25, 000 mmols of Na daily and it is essential to reabsorb > 99% of the filtered load to maintain circulating blood volume and BP. This is even more critical in hot and dry environments in Africa where salt is a scarce resource. It is highly heritable, with considerable differences in Africans when compared with Europeans. Na is reabsorbed along the entire nephron, and the Epithelial Na Channel (ENaC) is the final regulator making it an attractive candidate gene. In South Africa a variant of the beta ENaC (SCNN1B) (R563Q) causes low renin/low aldosterone RHT (a Liddle variant) in 6% of Blacks in urban South Africa and responds to treatment with amiloride. However, this variant is present in 20% of the indigenous Khoisan people of the Kalahari, and not associated with hypertension in their rural desert environment where access to salt is scarce. Furthermore GRK-4 regulates Na reabsorbtion in the proximal tubule, and variants are associated with low renin hypertension, impaired Na excretion and response to Na restriction. These variants are highly prevalent in South African black population compared to whites. Primary aldosteronism due to adrenal hyperplasia with low renin and elevated aldosterone is also more common in African Americans, but few data is available from Africa. These observations suggest a more physiological approach to treatment of low renin resistant hypertension in Africans with spironolactone and amiloride dependent on renin and aldosterone levels.